The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1143/jjap.50.055801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Soft X-rays on Highly Hydrogenated Diamond-Like Carbon Films

Abstract: The effect of soft X-ray irradiation of diamond-like carbon films in vacuum was investigated using synchrotron radiation (SR). Etching and the desorption of hydrogen upon SR exposure in vacuum occurred in highly hydrogenated diamond-like carbon (H-DLC) films; these processes were not observed in the irradiation of a low-hydrogenated DLC film. The extent of decrease in hydrogen content due to SR exposure was found to decrease with increasing the etching ratio of the H-DLC film. This indicates that hydrogen deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…As described in the introduction, the exposure to SR causes the volume of the H-DLC film to shrink because of the desorption of hydrogen [ 21 , 22 ]. Therefore, the dose dependence of the hydrogen content is the most notable factor when discussing the effect of SR on hydrogenated Si-DLC films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the introduction, the exposure to SR causes the volume of the H-DLC film to shrink because of the desorption of hydrogen [ 21 , 22 ]. Therefore, the dose dependence of the hydrogen content is the most notable factor when discussing the effect of SR on hydrogenated Si-DLC films.…”
Section: Resultsmentioning
confidence: 99%
“…DLC films have been considered to be durable against X-ray exposure [ 20 ]. However, our group has studied the effect of irradiation of H-DLC films by soft X rays and found that: (1) the volume of the H-DLC film is reduced under irradiation by soft X-rays; (2) the main reason for the volume reduction is desorption of hydrogen; and (3) new bonds between carbon atoms are formed by desorption of hydrogen, and the sp 2 /sp 3 ratio of carbon in the film increases [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The films were deposited at 200 nm thickness on Si wafers using CH 4 and C 2 H 2 gases by using an [31]. The hydrogen content of these films were estimated to be greater than 40 at.% using the combination of Rutherford backscattering spectrometry (RBS) and elastic recoil detection analysis (ERDA) of DLC films by using the same synthesis method [7].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…DLC films having large amounts of hydrogen were reported modified by the exposure to synchrotron radiation (SR) in the soft X-ray region [7]. The most important factor in causing deterioration of the material in low Earth orbit (LEO), where artificial satellites and spacecraft are positioned, is atomic oxygen exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The film had a low sp 2 content (graphite bonding) and no H content. This is important as recent studies indicate that DLC films containing H may be modified by x-ray irradiation [4].…”
Section: Experimental Methodsmentioning
confidence: 99%